High Efficiency Isolated Three Port Dc-Dc Converter For Dc Charger Stations - Ahmad Redzuan, Abdul Razak (2022)
The world energy crisis resulting the global warming and climate change. The renewable energy growth is capable to overcome the energy crisis. One of the technology renewable energies is electric vehicle (EV) where the demand for EV sales has increased every year. The charging technology need to be improved due to the existing alternating current (AC) charger has slow charging and limited to the low application. Besides that, the safety of consumers and equipment should also be emphasized due to current non-isolated DC-DC converter have safety issue. Therefore, the 100kW DC charger system based on isolated dual active bridge (DAB) DC-DC converter have been developed using MATLAB/Simulink software. Since the multiport EV charger have been concerned, the DAB has been expanded to three ports EV DC charger, known as triple active bridge (TAB) DC-DC converter is established. The TAB is introduced to overcome the complex configuration of the existing multiport converter that involving multiple conversion stage. Both DAB and TAB are modulated using single-phase shift (SPS) modulation and tested under various of phase-shift angle. Then, the efficiency of TAB is evaluated under several load systems which 25kW, 50kW, 75kW and 100kW. In overall, the TAB with 100kW load system have the higher efficiency compared to others by producing 86%, while the system with 75kW have the lowest efficiency with 66%.